Squared sine logistic map - de Carvalho, R. Egydio [UNESP]; Leonel, Edson D. [UNESP] (Elsevier, 2016)
A periodic time perturbation is introduced in the logistic map as an attempt to investigate new scenarios of bifurcations and new mechanisms toward the chaos. With a squared sine perturbation we observe that a point attractor reaches the chaotic attractor without following a cascade of bifurcations. One fixed point of the system presents a new scenario of bifurcations through an infinite sequence of alternating changes of stability. At the bifurcations, the perturbation does not modify the scaling features observed in the convergence toward the stationary state.
Keywords: Attractor; Bifurcation; Multi-stability; Perturbed logistic map